Evaluasi Kinerja Perbankan Syariah Di Indonesia dengan Pendekatan Islamicity Performance Index - Novianty, Lita Patricia; Isnaini, Desi (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2022)
This study aims to determine the performance of Islamic Banking In Indonesia with the IsIamicity Performance Index approach with the ratio of P.S.R., Z.P.R., E.D.R., and I.I.C. This research method uses a quantitative approach. The type of research used is descriptive research with a quantitative approach. The data used is secondary data in the form of the annual report statements of Islamic banking for the 2016-2020 period. The samples in this study were three banks. The results show that the Profit Sharing Ratio (P.S.R.) of B.C.A. Syariah Bank and Bank MuamaIat Indonesia get a good predicate with a value of >30%. In the Zakat Performance Ratio (Z.P.R.), all samples get an insufficient predicate with a discount of <35% The EquitabIe Distribution Ratio (E.D.R.) Qardh and Donations, all models received a vague predicate with a value of <35%. The equitable Distribution Ratio (E.D.R.) of all samples of the workforce also received an unfordable predicate with a value of <35%. fair Distribution Ratio (E.D.R.) The net profit of all pieces received an insufficient predicate with a value <35%. In the ratio of Islamic Income vs. Non-Islamic Income, all models get an excellent predicate with a value of >35% and an average of 99.98%